ANALISIS PARAMETER PEMESINAN MESIN CNC LASER DENGAN CONTROLLER ARDUINO UNO PADA BENDA KERJA AKRILIK DENGAN TEBAL 3 MM - HT Saragi, Jandri Fan; Dairi Boangmanalu, Eka Putra; Pratama, Angga Bahri; Sahat, Sahat (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
CNC (Computer Numerical Control) machines have revolutionized manufacturing processes and mechanical engineering by replacing manual methods that rely on human labor. A significant innovation in CNC technology is the use of lasers, which are highly beneficial in the engraving industry. CNC Laser machines are used to etch materials like 3 mm thick MDF boards according to predetermined design patterns. The precision level, removal rate, and engraving quality depend on the material properties, laser source characteristics, and laser parameters. The objective of this research is to determine the appropriate machining parameters for 3 mm thick MDF boards and to identify the optimal working time for engraving on this material. The method used in this study is the experimental method. The results of this research show that the feed rate used is 750 mm/min and the laser power is set at 40%, with a processing time of 4 minutes and 42 seconds to complete the engraving of a logo on a 3 mm thick MDF board.